2016
DOI: 10.1111/cei.12878
|View full text |Cite
|
Sign up to set email alerts
|

Circulating immune cells in multiple sclerosis

Abstract: Summary Circulating T and B lymphocytes contribute to the pathogenesis of the neuroinflammatory autoimmune disease, multiple sclerosis (MS). Further progress in the development of MS treatments is dependent upon a greater understanding of the immunological disturbances that underlie the disease. Analyses of circulating immune cells by flow cytometry have revealed MS‐associated alterations in the composition and function of T and B cell subsets, including temporal changes associated with disease activity. Distu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
62
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 100 publications
1
62
1
Order By: Relevance
“…In contrast to results of the current study, transitional B cells have been reported at lower frequency in CIS and relapsing–remitting MS by one group 27 but at similar frequency to HC by another 28 . Shifts within the B‐cell compartment reportedly occur in a temporal relationship with MS disease activity 5 . Thus an increase in circulating transitional B cells may indicate increased B‐cell release from the bone marrow in response to migration of mature B cells to sites of inflammation.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to results of the current study, transitional B cells have been reported at lower frequency in CIS and relapsing–remitting MS by one group 27 but at similar frequency to HC by another 28 . Shifts within the B‐cell compartment reportedly occur in a temporal relationship with MS disease activity 5 . Thus an increase in circulating transitional B cells may indicate increased B‐cell release from the bone marrow in response to migration of mature B cells to sites of inflammation.…”
Section: Discussioncontrasting
confidence: 99%
“…Functional impairment of Treg cells is commonly reported in MS studies; however, conventional analyses have failed to describe corresponding phenotypic characteristics 5 . In light of the work by Sakaguchi and colleagues, 11 it was our hypothesis that conventional definitions, such as those used in previous MS studies, obfuscate the functional heterogeneity of FoxP3 + Treg cells and that the CD45RA/FoxP3 fraction approach to analysis would yield more informative results.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Multiple sclerosis (MS) is a chronic inflammatory autoimmune disease of the central nervous system (CNS) characterized by damage to the brain and spinal-cord white matter and thus causing significant neurologic impairment and disability [1,2]. In MS, cytokines and chemokines produced by activated myelin-reactive CD4+ helper T (Th) lymphocytes play a crucial role in triggering the disease onset, as well as in further development of the disease.…”
Section: Introductionmentioning
confidence: 99%